“EGG-GRADING” Mesin Klasifikasi Telur Ayam (Berat Telur dan Telur Rusak) Otomatis Berbasis Microcontroller - Zulfa Ludfi Diana Sari Teknik Mesin (Retii, 2019)
ABSTRACT Eggs are one of the foods derived from poultry and is a popular source of animal protein food and is very popular with the public. Many of the people who open businesses as chicken egg breeders. The business will be marketed to consumers by sorting beforehand, both from the weight equality and sorting between eggs both rotten and rotten. However, in doing this sorting, chicken egg entrepreneurs still do it the conventional way, namely by using hand palms and lighting lamps. So it is very ineffective and inefficient. Therefore, in this study an egg grading machine was designed, which is a machine that is able to work for egg sorting based on the good and bad conditions of eggs and based on egg weight. This machine works automatically, by utilizing a microcontroller accompanied by the use of weight sensors and light sensors. Weight sensor here which works as an egg sorter based on the type of weight. While the light sensor works in the process of selecting good and bad eggs. This machine was made due to lack of egg grading machine production. It is known that the market of the egg grading machine is still on the market of China and Europe with prices that are still high. So by making this machine it is expected to be able to meet the needs of the Indonesian market at a relatively cheap price. Keywords: Egg Grading, Microcontroller, Weight Sensor, Light Sensor